The Importance of Business Place Permits (SITU) for Home Industries in Petumbukan, Deli Serdang Regency - Rambe, Suria Ningsih; Jelly Leviza; Erna Herlinda; Purba, Hasim Purba; Sutiarnoto (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Every member of the community wants to live in prosperity with their entire family through various kinds of businesses, including home industries. Home Industry (IRT) is an activity carried out in the home, although in the end the Home Industry will be marketed outside the home. Home Industry (IRT) is an industry with a workforce of one unit to four people. This industry has very limited capital. If the activity goes on for a long time, there will be an impact on the home business, namely it is not registered and does not have an official permit from the Government. One of the Home Industries (IRT) is in Petumbukan, Deli Serdang Regency. This Home Industry is a food and snack business or is called a snack. This Home Industry (IRT) has the name RJ, which stands for the name of the owner, Raju. This Raju Home Industry has five workers. This Raju Home Industry Business starts from morning until evening. Besides producing food (light snacks) consisting of sweet potato chips and banana chips. Currently the Home Industry (IRT) is very rapidly developing in Indonesia in general and in the Deli Serdang Regency area in particular. With the proliferation of Home Industries in City Districts, they should understand their obligation to regulate Business Place Permits (SITU) because if the Home Industry has taken up its home business, it will benefit a lot, one of which is getting a loan / capital credit from Government bank. Therefore, through community service activities for Lecturers who are Compulsory to Serve which was carried out on Monday, September 21, 2020, socialization was carried out on how or procedures so that Home Industry (IRT) on Petumbukan Jalan Besar Number 46 can obtain a Business Place Permit (SITU). and partners understand the benefits that will be obtained after obtaining the Business Place Permit (SITU). Chaired by: Suria Ningsih, SH. MHum, and consisting of Erna Herlinda, SH. MHum, Dr. Jelly Leviza, SH. MHum, Prof. Dr. Hasim Purba, SH. MHum, Dr. Sutiarnoto, SH. MHum. The method used in this socialization activity was a focused discussion beginning with a lecture and continued with direct questions and answers with the participants.